Profiles of mathematical identity among prospective mathematics teachers: A qualitative case study across mathematical ability levels - Santosa, Yoga Tegar; Setyaningsih, Nining; Kholid, Muhammad Noor (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: This study aims to explore how prospective mathematics teachers construct their mathematical identity at different levels of mathematical ability. The research focuses on five key components of mathematical identity: interest, recognition, competence, performance, and belief about the nature of mathematics, and examines how these dimensions interact to shape teachers’ self-perception and readiness for professional practice. Method: A qualitative case study design was employed involving 46 undergraduate students from Mathematics Education programs in the Surakarta region, Indonesia. Three participants representing high, medium, and low mathematical ability levels were purposively selected for in-depth analysis. Data were collected through a non-routine mathematics test, a mathematical identity questionnaire, and semi-structured interviews. The analysis followed the Miles and Huberman interactive model through data reduction, data display, and conclusion drawing, supported by method triangulation for validity. Finding: The findings reveal variations in the formation of mathematical identity across ability levels. High-ability students demonstrated strong and stable identities characterized by internalized motivation, balanced recognition, and reflective competence. Medium-ability students showed partially developed identities influenced by contextual and social factors, while low-ability students exhibited fragile identities shaped by external motivation yet showed emerging reflective awareness. Significance: These findings highlight that mathematical identity develops dynamically through the interaction of cognitive ability, reflection, and social validation. The study emphasizes the need for identity-oriented pedagogical interventions such as guided reflection, peer teaching, and mentoring to strengthen reflective engagement and intrinsic motivation among prospective mathematics teachers.